STRATEGI PEMASARAN UMKM KAIN TENUN ENDEK KOLOK DI DESA BENGKALA KABUPATEN BULELENG BALI - Ni Putu Srinadi Dewi; Luh De Liska; Ni Luh Putu Cahayani; Ni Luh Putu Ratnasari; Ni Wayan Saba Astuti; Ni Ketut Wardani; Risaldus Geong; Yosepdreitson Garu (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Endek Kolok woven fabric is one of the unique cultural treasures of Bengkala Village, Kubutambahan District, Buleleng Regency, Bali. This product has unique cultural value because it is only produced by the deaf community (kolok) in the village. To preserve its authenticity and cultural identity, the production of this woven fabric is strictly controlled and not open to the public. This study aims to identify the marketing strategies employed by small and medium-sized enterprises (SMEs) producing Endek Kolok woven fabric, as well as the challenges they face. The method used is a descriptive qualitative approach with data collection techniques through interviews with SME actors and community leaders, as well as documentation of the production and promotion processes. The research results indicate that marketing strategies are still very limited to traditional marketing and are not directed toward digital marketing due to customary rules that restrict production to the kolok community. This indicates that the preservation of cultural values is prioritized over commercial expansion.